Diversidad de artrópodos asociados a traspatios con dominancia de árboles de durazno Prunus persica (Rosales: Rosaceae) en el Estado de México - Hernández-Cumplido, Johnattan; Cruz-Caballero, Mayte; Reyes-Hernández, Laura; Castellanos-Vargas, Iván (Instituto de Ecología, A.C., 2023)
Backyards are relevant for humans because the food they provide, and they can become biodiversity reservoirs. However, these agroecosystems have been poorly studied because the enormous variation in sizes and type of managements they receive from humans. The aim of this investigation was to evaluate arthropods abundance and richness associated to backyards with peach trees dominance Prunus persica (L.) Stokes in Mexico center during two seasons (dry and rainy). We sampled five backyards inside a human community by using pitfall traps which were served every month during twelve months (May 2017–May 2018). We found 3,263 individuals from nine orders and 175 morphospecies were identified. The most abundant and the richest orders were consistent between seasons Diptera, Coleoptera and Hymenoptera. Abundance did not show significant differences between backyards or between seasons. Although richness was not significantly different from the other backyards the backyard with intermediate coverage of peach trees showed the lowest diversity. Our diversity results compared to other studies conducted in extensive peach orchards show highest diversity. Backyards are important for the conservation not only of species appreciated by humans, but also, they function as refuges of arthropod diversity maintaining similar abundances even in times of low water availability as we found in this study. This without affect the small-scale production of fruit trees such as peach.